2018
DOI: 10.1130/ges01625.1
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic history of the northernmost part of the Harrat Rahat volcanic field, Saudi Arabia

Abstract: We present a detailed geologic investigation of Pleistocene to Holocene mafic volcanism within the northernmost part of the Harrat Rahat volcanic field, proximal to the city of Al-Madinah, Saudi Arabia. Our study area covers ~570 km 2 , and encompasses lava flows, scoria cones, and shield volcanoes of 32 mapped eruptive units consisting of continental, intraplate alkalic and tholeiitic basalts, hawaiites, and a mugearite that erupted from at least 1014 ± 14 ka to a single Holocene event at 1256 A.D. Typical la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…Park et al, 2007Park et al, , 2008Hansen et al, 2007Hansen et al, , 2008Hansen et al, , 2012Tang et al, 2016Tang et al, , 2018Tang et al, , 2019Kaviani et al 2018). Petrological studies of Cenozoic rocks in the Arabian Shield (Duncan et al, 2016;Downs et al, 2018) also support the hypothesis of a northward mantle flow. This possible northward flow of the upwelled material affects not only the upper mantle but also the crustal structure beneath the Red Sea and Arabian Shield.…”
Section: Widespread Regional Mantle Flow Beneath Afar Red Sea W Armentioning
confidence: 61%
“…Park et al, 2007Park et al, , 2008Hansen et al, 2007Hansen et al, , 2008Hansen et al, , 2012Tang et al, 2016Tang et al, , 2018Tang et al, , 2019Kaviani et al 2018). Petrological studies of Cenozoic rocks in the Arabian Shield (Duncan et al, 2016;Downs et al, 2018) also support the hypothesis of a northward mantle flow. This possible northward flow of the upwelled material affects not only the upper mantle but also the crustal structure beneath the Red Sea and Arabian Shield.…”
Section: Widespread Regional Mantle Flow Beneath Afar Red Sea W Armentioning
confidence: 61%
“…Tang et al () identified no high temperature in the upper‐mantle lid below the volcanic regions, indicating adiabatic ascent of magmas. Also, rapid ascent and eruption of magma is suggested by geochemical analyses (e.g., Downs et al, ; Duncan et al, ), indicating little interaction between hot magmas and the crust. Therefore, the involvement of a thermal anomaly in the triggering of the observed crustal S velocity decreases must be minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, age compilations of Cenozoic volcanic rocks with tectonic events manifests a northward propagation of the volcanism (Krienitz et al, ). Also, the spread of volcanic centers within northern Harrat Rahat demonstrates the distribution of the older basaltic vents in the south to younger northward (Downs et al, ). These evidences appear to support the model of lateral mantle flow.…”
Section: Discussionmentioning
confidence: 99%
“…The northern part of HR is marked by a linear vent axis trending N30°W (Figure a), subparallel to trends in the Neoproterozoic basement. 40 Ar/ 39 Ar age dates for lavas from northern HR are all younger than 1.2 Ma, with the majority of flows younger than 400 ka yet with only one confirmed Holocene eruption (Downs et al, ). Eruptions recurrence rates are estimated to be 2.5–3.2 ka (Stelten et al, ).…”
Section: Introductionmentioning
confidence: 99%